MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN PEMANFAATAN BARANG BEKAS SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR IPAS SISWA KELAS V - Febriyanthi, Ni Komang Novitariyani; Suastika, I Nengah; Dantes, I Nyoman (Jurnal Administrasi Pendidikan Indonesia, 2024)
The main problem in learning in elementary school is the low ability of creative thinking and science learning outcomes of students who still depend on conventional learning methods. Conventional teacher-centered approaches often lack space for students to develop creativity and understand concepts in depth. This study aims to test the effectiveness of the project-based learning model by utilizing used goods in improving students' creative thinking skills and science learning outcomes. The subjects of this study are 56 grade V students of SDN Cluster VIII Sukawati for the 2024/2025 Academic Year, which are divided into two groups: an experimental group that uses a project-based learning model and a control group that uses conventional learning. This study uses a pseudo-experimental method with a post-test only control group design, as well as data analysis through ANOVA and MANOVA statistical tests. The results showed that there was a significant difference in students' creative thinking ability and science learning outcomes between the experimental group and the control group. Students in the experimental group had an average score of 128 creative thinking ability, classified in the "Very High" category, and an average science learning outcome of 87.6, classified in the "High" category. In contrast, the control group showed lower results on both variables. The implications of this study show that the project-based learning model is effective in increasing student engagement, creativity, and in-depth understanding of science materials. Additionally, the use of second-hand items as part of a learning project provides opportunities for students to develop collaboration, innovation, and social responsibility skills. The results of this study can be a reference for teachers, schools, and education policymakers to adopt project-based learning methods as a more effective strategy in learning in primary schools.